RADIOGRAPHIC APPROACH FOR EVALUATING LUNG ABSCESS IN A PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Oktavinayu Sari Latif; Dini Rachma Erawati (International Journal of Radiology and Imaging, 2025)
Systemic lupus erythematosus is a complicated autoimmune disease that presents in various organs, one of which is the lungs. We reported a 20-year-old female patient complaining of cough with phlegm, shortness of breath, chest pain radiating to the right shoulder, and a fever two weeks before admission. The patient was examined by thoracic radiography and thoracic CT scan with contrast. They found cavities with air-fluid levels and ground-glass opacity around them, with the results of sputum microbiological examination showing Klebsiella pneumoniae infection. The patient was then given antibiotic therapy. During an evaluation a month after therapy, the air-fluid level reduced, but the consolidation remained. The patient underwent sputum microbiological examination again and presented with MDR Klebsiella pneumoniae, which was then given therapy according to the results of antibiotic sensitivity. At the evaluation, the consolidation reduced, and the patient experienced clinical improvement. Risk factors for lung abscess in SLE patients are immune dysregulation, disease activity, and immunosuppressive therapy given to patients. Both conventional radiographs and CT scans have their place for approaching the diagnosis of lung abscesses in SLE patients. Thus, they should be performed to consider the appropriate management for SLE patients.